Citizenship Attitudes and Social Inequality Among Moroccan University Students. Issue 2 (3rd April 2022) - Idrissi, Hajar; Takky, Salma; Idrissi, Hind
ABSTRACT: Drawing on social identity approach, comprising of social identity theory and self-categorisation theory, this article compares the ways in which public and private university students in Morocco approach the controversial relationship between citizenship and identity. By revealing students' self-identification and the role socio-economic factors have in this process, we seek to gain knowledge about the extent to which citizenship is perceived as a legal status as opposed to membership in a political community and how the transformation inherent in global market capitalism and the distribution of resources affect the youth's behaviours and attitudes towards social action. The sample represented the public and private dichotomy divide through 150 participants from four differently located Moroccan universities, namely Sidi Mohamed Ben Abdellah University, Mohammed V University, Al-Akhawayn University and International University of Rabat. Data were collected by means of a self-administered questionnaire and a semi-structured interview and were analysed using a mixed method approach to triangulate findings and ensure trustworthiness.